2009
DOI: 10.1002/ijc.24247
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative chemoradiation versus radiation alone for stage II and III resectable rectal cancer: A systematic review and meta‐analysis

Abstract: Combining chemotherapy with preoperative radiotherapy (RT) has a sound radiobiological rationale. We performed a systematic review and meta-analysis of trials comparing preoperative RT with preoperative chemoradiation (CRT) in rectal cancer patients. The Cochrane Central Register of Controlled Trials, Web of Science, Embase and Medline (Pubmed) were searched from 1975 until June 2007. Dichotomous parameters were summarized using the odds ratio while time to event data were analyzed using the pooled hazard rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 38 publications
2
45
0
2
Order By: Relevance
“…Contrary to the belief that reduction in local recurrence after radiation increases the likelihood of overall survival, no significant effect in terms of overall survival was found from SRT approach compared with selective postoperative radiation ± chemotherapy [17]. The result was similar with prior meta-analyses [11][12][13][14]. This finding seems to be reasonable, considering the following facts.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Contrary to the belief that reduction in local recurrence after radiation increases the likelihood of overall survival, no significant effect in terms of overall survival was found from SRT approach compared with selective postoperative radiation ± chemotherapy [17]. The result was similar with prior meta-analyses [11][12][13][14]. This finding seems to be reasonable, considering the following facts.…”
Section: Discussionsupporting
confidence: 76%
“…The Colorectal Cancer Collaborative Group and Wong et al conducted literature-based meta-analyses that focused on preoperative radiation, and they found beneficial effects on local control compared to surgery alone [11,12]. Then, meta-analyses by De Caluwé et al and Ceelen et al demonstrated that preoperative CRT improves local control in resectable stage II and III rectal cancer compared to preoperative RT alone [13,14]. Nevertheless a metaanalyses by Chen et al based on eight randomized controlled trials involving 6894 patients found that short course radiotherapy substantially reduced the risk of local recurrence compared with surgery alone or selective postoperative radiation ± chemotherapy, also this effect is also comparable when compared with long course chemo Although SRT has been shown to marginally improve survival over surgery alone in this meta-analysis, it must be emphasized that the Swedish trial was the only included trial that reported a significant improvement in survival, and there was evidence of heterogeneity across the included studies [16].…”
Section: Discussionmentioning
confidence: 99%
“…Since majority of the patients in the West nowadays receive neoadjuvant chemoradiotherapy, the most pertinent question regarding the benefit of postoperative chemotherapy remains unanswered by the studies described above. In light of several systematic reviews reporting no benefit of neoadjuvant chemoradiotherapy when compared to radiotherapy alone in terms of disease free and overall survival, the role of postoperative chemotherapy has come into question [30,31] . Five recent European trials (CHRONICLE, QUASAR, EORTC 22921, PROCTOSCRIPT, ICNRRT) enrolling 3143 patients with stage Ⅱ and Ⅲ rectal cancer investigated the benefits of postoperative chemotherapy after neoadjuvant chemoradiotherapy and surgery (Table 1) [10,12,3234] .…”
Section: Postoperative Chemotherapy After Neoadjuvant (Chemo)radiothementioning
confidence: 99%
“…The local control benefit of preoperative radiotherapy remains relevant even in the era of total mesorectal excision [3]. The addition of chemotherapy to preoperative conventional long-term radiotherapy has been demonstrated to be feasible, with enhanced tumoricidal effects [4]. The protracted venous infusion of 5-FU during radiotherapy has demonstrated substantial advantages over bolus 5-FU administration in an adjuvant setting and has been extrapolated to preoperative strategies [5].…”
Section: Introductionmentioning
confidence: 99%